(3QSGdI JhHjN MSf Hf eYdGs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd CWGd Gddg HbGg hCOGe JCjjOg hfYeGg hGdMeO ddg Ydi Pdc cKjQkG hUdhGJg Ydi QShdg hBdg hSde CYde GdTjN Cfg hUd MSf Hf eYdG heYg BNQ adG CMSf Gddg LRGg s
(3BNQgG (B:s
(3hfMf fNUc HCJe GdSdGe hcPdc ef YfOfG jNUhc HCJe GdJMjI hGdMeO ddg QH GdYGdejf hJYQa GdLeGYI CffG dh hLOfG ef ffaP eYg GdcJGH dCfaPfGg hdhdG GdNTjI ef GdJaQjW ajg CfaPfGg ai GdJQJjH hGdSdGe JeJ HMeO Gddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B80s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis